2017
DOI: 10.1007/s10195-017-0465-8
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for the Oxford Hip Score after total hip replacement surgery: a novel approach to postoperative evaluation

Abstract: Background This is a prospective cohort study to define the thresholds to distinguish patients with a satisfactory or unsatisfactory outcome after total hip replacement (THR) based on patient-reported outcome measures (PROMs) including the Oxford Hip Score (OHS), and using patient satisfaction and patient-perceived function as global transition items. The thresholds are intended to be used as a tool in the process of determining which patients are in need of postoperative outpatient evaluation. Methods One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
4
6
0
6
Order By: Relevance
“…Our results are in line with previously published reports, showing significant improvement of OHS and EQ-5D (above 36 and 0.8, respectively) at early-term after primary hip replacement, 16,17,21–23 which is maintained over the long-term, 24 with over 70% reaching MCID and PASS thresholds for the OHS, 21 and approximately 90% of patients satisfied or very satisfied at 12 months follow-up. 9 Judge et al 21 found a mean improvement of +19 (10) points in OHS from 20 to 39, 70% of patients having reached MCID, and 74% having reached PASS at 6 months follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with previously published reports, showing significant improvement of OHS and EQ-5D (above 36 and 0.8, respectively) at early-term after primary hip replacement, 16,17,21–23 which is maintained over the long-term, 24 with over 70% reaching MCID and PASS thresholds for the OHS, 21 and approximately 90% of patients satisfied or very satisfied at 12 months follow-up. 9 Judge et al 21 found a mean improvement of +19 (10) points in OHS from 20 to 39, 70% of patients having reached MCID, and 74% having reached PASS at 6 months follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…9 Judge et al 21 found a mean improvement of +19 (10) points in OHS from 20 to 39, 70% of patients having reached MCID, and 74% having reached PASS at 6 months follow-up. Similarly, Beard et al 16 found an increase in OHS of + 20 (10) from 18 to 38, and Kjærgaard et al 22 found that 71% of patients reached MCID and 74% reached PASS at 6 months follow-up. Paulsen et al 17 found an increase of 0.28 for EQ-5D Index from 0.60 to 0.88 at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 87%
“…This observed improvement is greater than the previously reported minimum clinically important difference for the OHS which has been reported as 11 points [26], suggesting that these results were not only statistically, but also clinically significant. In addition, the mean post-operative OHS, which would be classified as good joint function according to the original description of the OHS [9], is comparable with previously reported OHS following THA in older patients [27], and is higher than previously reported threshold values for satisfaction following THA [28]. This suggests that very young patients undergoing THA using cemented stems can expect good functional improvement following their surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Da es jedoch in unserer Arbeit nicht darum geht, wie zufrieden ein Patient zu einem gewissen Zeitpunkt ist, sondern vielmehr darum, Patienten frühzeitig zu detektieren, die weitere Interventionen benötigen, teilen wir die Schlussfolgerung von Keurentjes et al nicht, sondern verstehen vielmehr die ausgewählten Scores als wertvolles Werkzeug. Kjærgaard et al 3 haben in einer Untersuchung eine vergleichbare Fragestellung bearbeitet. Es sollten Schwellenwerte als Werkzeug bei der Bestimmung von Patienten, die eine postoperative ambulante Untersuchung benötigen, definiert werden.…”
Section: Diskussionunclassified
“…Nach hüftendoprothetischer Versorgung von Patienten kann auf zahlreiche Messinstrumente zurückgegriffen werden, um das klinische Ergebnis des operativen Eingriffs zu bewerten. Neben der radiologischen Bewertung des Implantates, dem Bewegungsausmaß und der Gehstrecke rückt auch die subjektive Bewertung seitens des Patienten zur Beurteilung des Behandlungsziels immer mehr in den Fokus 1 , 2 , 3 . Da die Erhebung und die anschließende Auswertung von sog.…”
Section: Introductionunclassified